Comparative Study of Non-Productive Tool Path Length for Contour Parallel Machining / Haslina Abdullah...[et al.] - Abdullah, Haslina; Ramli, Rizauddin; Abd Wahab, Dzuraidah; Abu Qudeiri, Jaber (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Reduction of machining time is significant for increasing the efficiencies of a machining process. It can be minimized by the rise with the cutting speed or decrease the tool path length. This paper presents an optimization method of non-productive tool path length during contour parallel offset machining by minimizing the tool retraction based on Ant Colony Optimization (ACO). The optimization of the tool retraction is modeled as an application of the Travelling Salesman Problem (TSP). To assess the performance of the proposed method, the length of the non-productive tool path obtained by ACO is compared with traditional computer-aided manufacturing (CAM) software. It can be ascertained that the ACO method generates a non-productive tool path length that is approximately 20% better than the conventional method.